2019
DOI: 10.7287/peerj.preprints.27555
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Polyamines and legumes: Joint stories of stress, nitrogen fixation and environment

Abstract: Polyamines (PAs) are natural aliphatic amines involved in many physiological processes in almost all living organisms, including responses to abiotic stresses and microbial interactions. This review presents the profuse evidence that relates changes in polyamines levels during responses to biotic and abiotic stresses in model and cultivable species within Leguminosae, and examines their potential roles in the functioning of symbiotic interactions with nitrogen fixing bacteria and arbuscular mycorrhizae. The fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 80 publications
(86 reference statements)
0
1
0
Order By: Relevance
“…Coarse and high-resolution mapping approaches utilised herein facilitated the validation of genomic regions for Δ 13 variation and delimited candidate genes in canola, which are implicated in leaf-level WUE (Hersen et al, 2008; Cutler et al, 2010; Youn et al, 2016; Tao et al, 2018; Menéndez et al, 2019). For example, this study identified and validated a QTL that influences multiple traits; Δ 13 C, days to flower, plant height and seed yield on chromosome A09 that map within 92 kb of the ERECTA gene (Table S13).…”
Section: Discussionmentioning
confidence: 99%
“…Coarse and high-resolution mapping approaches utilised herein facilitated the validation of genomic regions for Δ 13 variation and delimited candidate genes in canola, which are implicated in leaf-level WUE (Hersen et al, 2008; Cutler et al, 2010; Youn et al, 2016; Tao et al, 2018; Menéndez et al, 2019). For example, this study identified and validated a QTL that influences multiple traits; Δ 13 C, days to flower, plant height and seed yield on chromosome A09 that map within 92 kb of the ERECTA gene (Table S13).…”
Section: Discussionmentioning
confidence: 99%